Use of linearised quasi-geostrophic numerical model for evaluation of truncation errors - SALVEKAR, PS (MAUSAM, 1986)
A linear, quasi-geostrophic, multilayer, numerical model which has been developed in an earlier study (Mishra & Salvekar 1980) for investigating baroclinlc instability mechanism of mean monsoon zonal flow, is used here to obtain vertical and time truncation errors in gowth rate and phase velocity of a baroclinic unstable wave that arise due to finite difference approximations.